2019
DOI: 10.4103/ams.ams_250_18
|View full text |Cite
|
Sign up to set email alerts
|

Immediate functional loading: Results for the concept of the strategic implant®

Abstract: Background: Immediate functional loading of one-piece dental implants has become an accepted treatment modality for fixed restorations in fully edentulous mandibles and maxillae. Nevertheless, studies regarding immediate loading procedures in extraction sites in both the jaws, as well as in segment reconstructions and single-tooth replacements, are limited. Purpose: The purpose of this study was to evaluate the presently used protocol for immediate functional loading (w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 6 publications
(5 reference statements)
2
42
0
1
Order By: Relevance
“…The strongest anchorage obtained with basal implants offers stable occlusal units leading to good chewing function. 12,13,16,18,21 Most of the patients in our study reported a significant improvement in their satisfaction with mastication from average to excellent after basal implant treatment, a finding that matches the findings of S. Ihde and A. Ihde 12,18 and Scortecci 15 and is in accordance with other studies on endo-osseous implant treatment showing improved mastication with implant-supported prostheses. 55−59 Since speech is usually affected by edentulism, improving patients' speech is one of the main purposes of replacing missing teeth.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The strongest anchorage obtained with basal implants offers stable occlusal units leading to good chewing function. 12,13,16,18,21 Most of the patients in our study reported a significant improvement in their satisfaction with mastication from average to excellent after basal implant treatment, a finding that matches the findings of S. Ihde and A. Ihde 12,18 and Scortecci 15 and is in accordance with other studies on endo-osseous implant treatment showing improved mastication with implant-supported prostheses. 55−59 Since speech is usually affected by edentulism, improving patients' speech is one of the main purposes of replacing missing teeth.…”
Section: Discussionsupporting
confidence: 90%
“…Basal implants have been prescribed as an alternative treatment for these patients with a high success rate, less severe complications, and lower cost and number of surgeries. [12][13][14]20,21 There is an increased need for clinical research to evaluate patient satisfaction and quality of life in relation to this treatment modality as a major parameter indicating implant success.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many implant systems have been developed and distributed in the dental market, one of which is the basal implant [12][13][14][15][16][17][18][19][20][21][22]. In this system, the implant is anchored to the basal/cortical bone [12][13][14][15][16][17][18][19][20][21][22] which is useful in cases of severe alveolar ridge resorption, when bone grafting is prohibited due to the patient's general medical condition and when a more conservative treatment with lower cost is needed [12-14, 16, 20-22]. e BCS ® implant is a special type of basal implant, consisting of one piece that is inserted through a crestal approach, just like the other endo-osseous implants and then anchored deeply inside the basal bone through its horizontal plates [12][13][14]19].…”
Section: Introductionmentioning
confidence: 99%